Lignocellulose degradation patterns, structural changes, and enzyme secretion by Inonotus obliquus on straw biomass under submerged fermentation. (October 2017) - Xu, Xiangqun; Xu, Zhiqi; Shi, Song; Lin, Mengmeng
Graphical abstract: Highlights: Degradation patterns and structures of three straw biomass were compared. Lignin in wheat straw was selectively and effectively degraded. Crystalline cellulose in rice straw was significantly decreased. Degradation was in line with the production of ligninolytic and hydrolytic enzymes. Abstract: This study examined the white rot fungus I. obliquus on the degradation of three types of straw biomass and the production of extracellular lignocellulolytic enzymes under submerged fermentation. The fungus process resulted in a highest lignin loss of 72%, 39%, and 47% in wheat straw, rice straw, and corn stover within 12 days, respectively. In merely two days, the fungus selectively degraded wheat straw lignin by 37%, with only limited cellulose degradation (13%). Fourier transform infrared spectroscopy revealed that the fungus most effectively degraded the wheat straw lignin and rice straw crystalline cellulose. Scanning electronic microscopy showed the most pronounced structural changes in wheat straw. High activities of manganese peroxidase (159.0 U/mL) and lignin peroxidase (123.4 U/mL) were observed in wheat straw culture on Day 2 and 4, respectively. Rice straw was the best substrate to induce the production of cellulase and xylanase.